Acquired Perforating Dermatosis in a Patient on Peritoneal Dialysis: A Case Report and Review of the Literature - Talha H. Imam; Hassan Patail; Nabeela Khan; Phillip T. Hsu; David S. Cassarino (Case Reports in Nephrology)
Acquired perforating dermatosis (APD) is a debilitating and itchy skin disease. Its diagnosis is based on biopsy and the treatment is not very clear. It is not well established as to how wide spread it is in patients on peritoneal dialysis (PD) and its implications in this population have not been well studied. Here we present a case of APD that developed in a patient on PD. Its pathology and treatment options are reviewed. More studies are needed to assess the prevalence of APD in PD population.